Secnidazole Oral Granules: A Novel Drug Formulation and an Effective Alternative in Treatment of Bacterial Vaginosis - Singh, Vishal K; M Singh, Kritarth Naman; Shetty, Yashashri C (International Journal of Innovative Research in Medical Science, 2018)
Bacterial vaginosis (BV) is one of the common cause of abnormal vaginal discharge which enhances the acquisition and transmission of a range of sexually transmitted infections. The currently available antibiotics for BV must be administered to patients for 5 to 7 days and studies have shown that nearly 50% patients do not comply with this lengthy treatment regimen. Secnidazole, a second-generation 5-nitroimidazole is developed in a novel oral granule formulation with a broad spectrum of activity against anaerobic bacteria. Based on the phase II and phase III data this molecule received its US FDA approval in September 2017. Secnidazole oral granules offers a valuable advantage since it has longer half-life (∼17 hours) which makes it suitable for single-dose therapy and also has a novel method of administration where the granules taken orally by sprinkling onto yogurt or pudding, without regard to the timing of meals. Also, it does not interfere with combined oral contraceptive and spares lactobacilli, a characteristic which is desirable in drugs used to treat BV. The complexity of current treatment regimen can decrease the patient’s compliance and a single dose treatment option with secnidazole oral granules may improve treatment adherence, which may be beneficial for both patients and health care practitioners. Secnidazole is the first new oral antibiotic to treat BV in more than a decade and will provide physicians with a new treatment option. This review was conducted by searching the databases of PubMed, EMBASE, and Google Scholar for articles.